Perancangan Tata Letak Fasilitas Pada PT. Lima Jaya - Jonathan Wijaya Gunawan; tanti octavia; felecia felecia (Jurnal Titra, 2015)
PT.Lima Jaya is a company that engaged in the field of steel and metalworks. Currently, this company wants to build a new company that specialized in wiremesh production. Therefore, this research tries to design their facility layout for minimizing moment. Three algorithms are applied in order to get the best result. The algorithms are corelap algorithm, aldep algorithm, and blocplan algorithm. The result shows that the blocplan algorithm gives the best result with the moment 13579,4.